Preparation of chemically modified Macadamia nutshells for adsorptive removal of selected heavy metals - Ntuli, Themba Dominic (Vaal University of Technology, 2017)
The abundance of agricultural waste materials has led to its use as adsorbents for trace metal adsorption. The raw Macadamia nutshell (RMN) powder was treated with a hydrochloric acid solution to obtain acid modified Macadamia nutshells (AMM), and with sodium hydroxide solution to obtain base modified Macadamia nutshells (BMM). Then, the AMM and BMM materials were grafted with 0.5 M, 1 M, and 2 M acrylic acid. The different AMM grafted materials were labelled 0.5 GAM, 1 GAM and 2 GAM representing the different grafting ratios. The same naming order was followed for the BMM grafted materials, that is, 0.5 GBM, 1 GBM and 2 GBM corresponding to different concentrations used. The prepared Macadamia based adsorbents were characterized using Fourier transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), carbon, hydrogen, nitrogen and sulphur (CHNS) analysis, powder X-ray diffraction (PXRD), scanning electron microscopy (SEM), and Brunauer-Emmett-Teller (BET) analysis. The determination of surface properties such as the point of zero charge (pHPZC), bulk density and the surface negative charge was accomplished with appropriate wet chemistry methods. The adsorption of selected trace metals (Cu(II), Cd(II), Co(II), and Cr(VI)) was done in batch experiments. Atomic absorption spectroscopy (AAS) was used for the determination of metal ions concentrations and total Cr. The ultraviolet-visible (UV–Vis) spectroscopy was used for the determination of Cr(VI) concentration remaining in solution after adsorption. The RMN, AMM, and BMM adsorbents showed potential in removing more than 45% Cu(II) ions, but less than 30% for both Cd(II) and Co(II) ions. However, more than 90% removal of Cr(VI) ions was achieved with the same adsorbents. Consequently, only the adsorption of Cr(VI) was further investigated in the study due to the higher removal efficiency displayed by the Macadamia based biosorbents. The optimum adsorption conditions for the RMN, AMM, and BMM materials were found to be pH 2, 100 mg/L initial concentration of Cr(VI), 600 min contact time and 0.2 g adsorbent mass. The ideal conditions for the 0.5 GAM and 0.5 GBM were found to be pH 2, 25 mg/L initial concentration of Cr(VI), 180 min contact time, and 0.15 g adsorbent mass. The optimum temperature was found to be 40℃ for all materials. A volume of 20 mL was used for all batch experiments. The RMN, AMM, BMM, 0.5 GBM, and 0.5 GAM adsorption mechanisms were better described by the Langmuir isotherm which predicted a monolayer sorption process. The kinetic data fitted better to the pseudo second-order rate model which signified a chemisorption type of interaction. The thermodynamic parameters showed that the adsorption reaction was feasible, spontaneous and endothermic. The Macadamia based materials showed greater potential as adsorbents for the adsorption of Cr(VI) ions from aqueous solution compared to the other selected trace metal ions [Cd(II), Cu(II) and Co(II)].
M. Tech. (Chemistry, Faculty of Applied and Computer Science), Vaal University of Technology
Keywords: Macadamia nutshell, chemically modified, heavy metals, adsorption (physical and chemical); Macadamia nut; Plants -- Effect of trace elements on; Heavy metals; Chemisorption